Advances in electron channelling contrast imaging and electron backscatter diffraction for imaging and analysis of structural defects in the scanning electron microscope. Issue 1 (July 2020) - Trager-Cowan, C; Alasmari, A; Avis, W; Bruckbauer, J; Edwards, P R; Hourahine, B; Kraeusel, S; Kusch, G; Jablon, B M; Johnston, R; Martin, R W; Mcdermott, R; et al.
Abstract: In this article we describe the scanning electron microscopy (SEM) techniques of electron channelling contrast imaging and electron backscatter diffraction. These techniques provide information on crystal structure, crystal misorientation, grain boundaries, strain and structural defects on length scales from tens of nanometres to tens of micrometres. Here we report on the imaging and analysis of dislocations and sub-grains in nitride semiconductor thin films (GaN and AlN) and tungsten carbide-cobalt (WC-Co) hard metals. Our aim is to illustrate the capability of these techniques for investigating structural defects in the SEM and the benefits of combining these diffraction-based imaging techniques.